Bittersweet cocoa: Certification programmes in Ghana as battlegrounds for power, authority and legitimacy. Issue 136 (November 2022) - Amuzu, David; Neimark, Benjamin; Kull, Christian
Abstract: Critical studies on the interlinkages of access, power and sustainability in high value tropical commodity systems are gaining traction in the academic literature. This article draws on access theory to examine how the distributional effects of a private sector certification programme on rural cocoa growing communities are bound up in the power relations between the state, private sector actors and smallholders in Ghana. The article is based on a qualitative case study approach involving 40 semi-structured interviews, 20 in-depth interviews and field observations conducted between 2018 and 2021. We found that the private sector firm certification incentives such as premiums, agronomic inputs and technical services are distributed unevenly, and also contribute to increased production costs, theft, unjust gender relations, and labour exploitation. We argue that the certification programmes obfuscate the deteriorating relations between the state and the farmers and enable the private firms to gain foothold and affirm their operational legitimacy and market links with smallholders. We conclude that revising the certification programmes would require market and institutional reform. The revision also needs to take into account the existing structural differences among farmers, and between the state and the market for better sustainable transitions.